Enhanced long-term potentiation and impaired learning in mice lacking alternative exon 33 of CaV1.2 calcium channel - Sheeja Navakkode; Jing Zhai; Yuk Peng Wong; Guang Li; Tuck Wah Soong (Translational Psychiatry, 2022)
Abstract The CACNA1C (calcium voltage-gated channel subunit alpha 1 C) gene that encodes the CaV1.2 channel is a prominent risk gene for neuropsychiatric and neurodegenerative disorders with cognitive and social impairments like schizophrenia, bipolar disorders, depression and autistic spectrum disorders (ASD). We have shown previously that mice with exon 33 deleted from CaV1.2 channel (CaV1.2-exon 33−/−) displayed increased CaV1.2 current density and single channel open probability in cardiomyocytes, and were prone to develop arrhythmia. As Ca2+ entry through CaV1.2 channels activates gene transcription in response to synaptic activity, we were intrigued to explore the possible role of Cav1.2Δ 33 channels in synaptic plasticity and behaviour. Homozygous deletion of alternative exon 33 resulted in enhanced long-term potentiation (LTP), and lack of long- term depression (LTD), which did not correlate with enhanced learning. Exon 33 deletion also led to a decrease in social dominance, sociability and social novelty. Our findings shed light on the effect of gain-of-function of CaV1.2Δ 33 signalling on synaptic plasticity and behaviour and provides evidence for a link between CaV1.2 and distinct cognitive and social behaviours associated with phenotypic features of psychiatric disorders like schizophrenia, bipolar disorder and ASD.